1997
DOI: 10.3109/10826089709055866
|View full text |Cite
|
Sign up to set email alerts
|

“Substance Abuse” Disorders among Runaway and Homeless Youth

Abstract: This study used systematic sampling methods to recruit a sample of 432 homeless youth from both service and natural "hang-out" sampling sites. According to DSM-III criteria, the majority of respondents were classified as having an alcohol and/or illicit "drug abuse" disorder (71%). The results from multivariate logistic regression analyses indicate that cumulative length of time homeless is positively associated with risk for an "abuse" disorder. The implications of these findings and recommendations for servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
138
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(144 citation statements)
references
References 5 publications
5
138
1
Order By: Relevance
“…1 Relative to housed youth, these youth are at increased risk for a myriad of health and behavioral health problems, including substance abuse, sexually transmitted diseases, poor mental health outcomes, violence, and victimization. [2][3][4][5] Recent work among homeless adults has suggested that cell phone technology may present unique opportunities for working with transient populations. 6 As cell phones offer connections to others without the physical constraints of permanent dwellings, new communication patterns are feasible for homeless people, including access to social support, case management, and health professionals, which could in turn lead to improved health and behavioral health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…1 Relative to housed youth, these youth are at increased risk for a myriad of health and behavioral health problems, including substance abuse, sexually transmitted diseases, poor mental health outcomes, violence, and victimization. [2][3][4][5] Recent work among homeless adults has suggested that cell phone technology may present unique opportunities for working with transient populations. 6 As cell phones offer connections to others without the physical constraints of permanent dwellings, new communication patterns are feasible for homeless people, including access to social support, case management, and health professionals, which could in turn lead to improved health and behavioral health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the homeless population has a disproportionately higher risk of HIV transmission (Ebner and Laviage, 2003) and substance use (Kipke et al, 1997). Substance abuse has been associated as a risk factor for HIV, both in terms of drug and sexual related risk (Rotheram-Borus et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been found that the amount of time that youth spend on the street is positively related to both substance use and substance abuse (Kipke, Montgomery, Simon, & Iverson, 1997). It is possible that substance use eases the pain that many of these young people experience as a result of being on the street (Farrow et al, 1992;Kipke, Montgomery, et al, 1997).…”
Section: Hypothesized Modelmentioning
confidence: 99%